A Curious Case of Intestinal Diaphragm Disease Unmasked by Perforation of a Duodenal Ulcer - Mairéad McNally; Ion Cretu (Case Reports in Medicine)
Nonsteroidal anti-inflammatory drugs are a common cause of intestinal injury. A variety of NSAID-induced injuries may occur including ulcers, erosions, colitis, strictures, and diaphragm disease. Diaphragm disease refers to the development of multiple thin, concentric, stenosing strictures in the intestine. Strictures occur most often in the midintestine and are thought to be pathognomonic of NSAID damage. They can lead to intermittent or complete bowel obstruction. Diagnosis may be elusive as there is nothing specific about NSAID-induced injury at endoscopy and histology is also nonspecific. Even at laparotomy, the diagnosis of diaphragm disease may be missed as the serosa may appear normal and strictures can be difficult to palpate. While most NSAID-induced lesions tend to resolve quickly following withdrawal of the offending drug, diaphragm-like strictures usually require intervention such as stricturoplasty or surgical resection of the involved segment of bowel. Here we report the case of a 60-year-old male patient who presented with iron deficiency anaemia and recurrent subacute bowel obstruction. Following endoscopy and repeated CT scanning of his abdomen, he was diagnosed with Crohn’s disease. He was treated with 5-ASAs and immune suppression until a perforated duodenal ulcer resulted in emergency laparotomy and the subsequent discovery of multiple intestinal diaphragms attributable to long-standing NSAID use.